Educating the Next Generation of Accountants: Linking Learning Objectives and Cognitive Ability - Matthew J. Sargent; Bradley G. Winton (STIE Malangkucecwara, 2026)
Accounting students have historically had their cognitive ability examined through the lens of Bloom’s taxonomy. However, does a relationship exist between Bloom’s continuum of categories of cognitive processes and a student’s cognitive ability? This study aims to answer this question by investigating whether Bloom’s taxonomy aligns with an accounting student’s measured level of cognitive ability. The analytical focus of this study is to extract qualitative information from accounting students’ critical thinking exercises. This information provides the basis for analyzing whether textual evidence from accounting students based on Bloom’s taxonomy significantly relates to an assessment of cognitive ability. The implications of this research are both theoretical and practical in nature. From a theoretical perspective, this study provides evidence of the overlap between Bloom’s taxonomy and measurements of critical thinking and reflective judgment. In this understanding, accounting educators can refine their use of Bloom’s taxonomy when educating the next generation of accounting students. By analyzing each category and its relationship to cognitive ability, accounting educators can more effectively apply each level of Bloom’s framework to enhance critical thinking while also focusing on areas where there appears to be minimal overlap to maximize the development of cognitive abilities in students.